L' archivio di Filippo Ferrari e il cardinale Federico Borromeo agiografo (ms. Milano, Biblioteca Ambrosiana, L 22 suss.) - Barbero, Giliola (Analecta Bollandiana, 2006)
Federico Borromeo, archbishop of Milan from 1595 to 1631 and founder of the Biblioteca Ambrosiana, was very interested in hagiography and collected and edited many texts and materials which remained for the most part unpublished and which are presented here for the first time. Amongst the documents which he obtained is the huge archive assembled by Filippo Ferrari for the compilation of his Catalogus sanctorum Italiae published in 1613. It constitutes the greater part of codex Ambrosianus L 22 suss. An inventory of this archive made up of notes and transcriptions of hagiographic texts which are in general very rare is given.